Linking Farmers to Markets through Productive Alliances : An Assessment of the World Bank Experience in Latin America - World Bank Group (World Bank, Washington, DC, 2016)
This new report presents the results of a systematic assessment of the World Bank’s 15-year experience with the productive alliance approach adopted by 21 projects in 10 countries across Latin America and the Caribbean. With funding of over United States (U.S.) 1 billion dollar since the early 2000s, increasing evidence suggests that the productive alliance approach can lead to increases in productivity, market integration, and income of smallholder farmers. The findings of this report are based on a detailed overview and comparison of different productive alliance projects in terms of targeting strategies, subproject selection, implementation, monitoring, and evaluation. It provides valuable lessons on different design features and implementation experiences for future operations.